Trade liberalisation in Mexico: Rhetoric and reality - Penélope Pacheco-López; Anthony P. Thirlwall (University of Kent, Department of Economics, 2004)
This paper examines the process of trade liberalisation in Mexico, particularly since the mid-1980s and the signing of the NAFTA agreement, and its impact on economic performance. The average growth of GDP of the Mexican economy since liberalisation has been only one-half the rate pre-liberalisation and we attribute this deteriorating performance to a rise in the income elasticity of demand for imports (partly associated with an increase in foreign direct investment with a high import content) which has not been compensated by a sufficiently fast growth of exports, leading to severe balance of payments difficulties. Mexican exchange rate policy has not helped the situation.
Keywords: C22; F13; F14; F32; F43; 330; Trade liberalisation; Economic growth; Balance of payments; Foreign direct investment; Mexico; NAFTA; Außenhandelsliberalisierung; Wirtschaftswachstum; Direktinvestition; Zahlungsbilanz; Mexiko; NAFTA-Staaten